COVID-19 and Diabetes in Children: A Narrative Review - Mahin Hashemipour; Daniel Zamanfar; Houman Hashemian; Afagh Hassanzadeh Rad; Maryam Shahrokhi; Setila Dalili (Mazandaran University of Medical Sciences, 2022)
Background: COVID-19 is an unknown and novel virus that creates a challenge with all comorbid conditions, including diabetes mellitus (DM). Although DM has not been determined as a definite risk factor for COVID-19 in childhood, clinicians should consider the potential association between DM and COVID-19.  Objectives: This study aimed to review COVID-19 and DM comorbidity in children. Methods: ISI Web of Science, PubMed, and Google Scholar were investigated to find relevant articles regarding COVID-19 and DM. Results: Data revealed 50% higher fatal outcomes of COVID-19 in DM children than in healthy ones. Because of the importance of DM in children, it seems mandatory to consider type 1 diabetes and its consequences on COVID-19. Conclusions: Understanding the pathophysiology of COVID-19 and its interaction with DM are helpful for better management of the disease. These considerations can help clinicians make better decisions about the treatment modalities, management, and diabetic ketoacidosis treatment.